Internalisasi Nilai Pancasila dalam Pendidikan Tinggi sebagai Strategi Penguatan Karakter Kebangsaan di Era Digital - Ahmad Syaifuddin Zuhri; Nur Aini Masruroh; Muhammad Fikri Hamdani (PT. Panca Publishing Indonesia, 2026)
The digital era presents new challenges to the internalization of Pancasila values in higher education institutions in Indonesia. Purpose: This study aims to analyze strategies for internalizing Pancasila values through higher education programs as a means of strengthening national character in the digital era. Method: A qualitative approach with case study design was employed, involving 120 university students as respondents across five public universities in Java, using in-depth interviews, observations, and documentation. Results: The findings indicate that integrative curriculum strategies, digital literacy-based learning, and campus cultural activities significantly improve students' national character index by 34.7%. Conclusion: Internalization of Pancasila values through higher education requires a comprehensive approach that integrates formal learning, campus culture, and digital media. Educational institutions must adapt their strategies to digital transformation to maintain the relevance of national character education.